C‐Jun N‐terminal kinase and Akt signalling pathways regulating tumour necrosis factor‐α‐induced interleukin‐32 expression in human lung fibroblasts: implications in airway inflammation. Issue 2 (February 2015) - Li, Dagen; Chen, Dapeng; Zhang, Xuemei; Wang, Hong; Song, Zixin; Xu, Wenchun; He, Yujuan; Yin, Yibing; Cao, Ju
Summary Airway inflammatory diseases such as chronic obstructive pulmonary disease (COPD) and asthma are associated with elevated expression of interleukin‐32 (IL‐32), a recently described cytokine that appears to play a critical role in inflammation. However, so far, the regulation of pulmonary IL‐32 production has not been fully established. We examined the expression of IL‐32 by tumour necrosis factor‐α (TNF‐α) in primary human lung fibroblasts. Human lung fibroblasts were cultured in the presence or absence of TNF‐α and/or other cytokines/Toll‐like receptor (TLR) ligands or various signalling molecule inhibitors to analyse the expression of IL‐32 by quantitative RT‐PCR and ELISA. Next, activation of Akt and c‐Jun N‐terminal kinase (JNK) signalling pathways was investigated by Western blot. Interleukin‐32 mRNA of four spliced isoforms (α, β, γ and δ) was up‐regulated upon TNF‐α stimulation, which was associated with a significant IL‐32 protein release from TNF‐α‐activated human lung fibroblasts. The combination of interferon‐γ and TNF‐α induced enhanced IL‐32 release in human lung fibroblasts, whereas IL‐4, IL‐17A, IL‐27 and TLR ligands did not alter IL‐32 release in human lung fibroblasts either alone, or in combination with TNF‐α. Furthermore, the activation of Akt and JNK pathways regulated TNF‐α‐induced IL‐32 expression in human lung fibroblasts, and inhibition of the Akt and JNK pathways was able to suppress the increased release of IL‐32 to nearly the basal level. These data suggest that TNF‐α may be involved in airway inflammation via the induction of IL‐32 by activating Akt and JNK signalling pathways. Therefore, the TNF‐α/IL‐32 axis may be a potential therapeutic target for airway inflammatory diseases.